Wacana Iklan Parodi Jepang Fanta Gakuen Sensei Series - Dian Natashia (Bina Nusantara University, 2015)
Research aimed to understand the message sent by the sender by analyzing critically the substence used and built the situation inside Japanese parody advertisement titled Fanta Gakuen Sensei Series. This research used qualitative descriptive method and provided two parody advertisement videos as data. The data were described and analyzed with Guy Cook’s Advertising Discourse Theory to reveal the substance used and built the context and situation inside the advertisements and Foucault’s Power and Discipline Theory to understand the message trying to be conveyed by looking into relationship between teachers and students in Japan. Result of the analysis shows that to avoid monotonous advertisements, Fanta uses advertisements parodying a popular drama during that era and adding humor into them, so the receiver will remind it for a long time. This is not just persuasive, but the advertisement’s strategy in those advertisements is also informative and inviting the target group to think critically. Through social context, these advertisements are intended to remind children to be disciplined regarding their daily behaviors and to obey and respect their teachers all the time. The producer also intends to remind that during hardships or strange situation, children should not take them seriously and be happy with Fanta.